Kawasaki like illness due to COVID-19: a review of the literature - Yulin Fang; Veeraraghavan Meyyur Aravamudan; Gurusaravanan Kutti Sridharan; Keyur Kamlesh Mehta; Ramkumar Sekhar; Nagendra Boopathy Senguttuvan; Indumathi Venkatachalam; Muhammad Bilal Abid (Journal of Infection in Developing Countries)
Introduction: Viral infections have been described as triggers for Kawasaki Disease (KD), a medium vessel vasculitis that affects young children. Akin to the H1N1 pandemic in 2009, there is a similar rise in the incidence of KD in children affected with Coronavirus disease 2019 (COVID-19). Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-COV-2) has been reported to induce an exaggerated systemic inflammatory response resulting in multi-organ involvement, particularly initiated with pulmonary parenchymal damage. This review article will discuss KD-like manifestations in COVID-19 patients in the pediatric cohort.